Foreigner themes in the German joke. Based on the example of jokes about Turks - Sikorska-Bujnowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2016)
The article attempts to answer the question of what the themes of German jokes about Turks are and what role stereotypes play. The form of the joke and all means used to build humour, primarily incorrect forms used intentionally, are also important.